DIVERSITAS CAPUNG (ODONATA) DI SITU PAMULANG KOTA TANGERANG SELATAN, BANTEN - Narti Fitriana (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
Dragonflies is one indicator of the waters clean. This study aims to determine the diversity index of dragonfly in Situ Pamulang South Tangerang City, Banten. Data was collected using line transect method along the 400 m . observation was conducted on May up to November 2015. Dragonflies were collected using insect nets, identified was doing at Integrated Laboratory Center UIN Jakarta. Dragonfly found in Situ Pamulang were 15 species, 14 gerera, 4 family, 2 suborder, 279 individuals totally. The biodiversity index (H ') dragonfly in Situ Pamulang was 2.41 showed that the structure surrounding communities are very stable in both categories with a scale of 5. Brachythemis contaminate was common dragonfly there. Dragonflies tend to choose Ipomoea sp. as perch and landing.Keywords: anisoptera, diversity, dragonfly, Situ Pamulang, zygoptera